CCNA certification all-in-one for dummies - Angelescu, Silviu, 1945- (--For dummies., 2010)
"If you're planning to advance your career by taking the all-important Cisco Certified Network Associate (CCNA), this is the study guide you need! Seven minibooks cover all the concepts and topics on which you'll be tested, covering the latest version of the exam. Each part of the exam is covered thoroughly in its own section, so you can readily find the information you want to study"--Resource description page